2000
DOI: 10.1007/s004240000342
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A activates leptin-responsive neurons in the arcuate nucleus

Abstract: Orexins, also named hypocretins, are newly described neuropeptides, which are produced almost exclusively in neurons of the lateral hypothalamus and have been shown to increase food intake after intracerebroventricular injection. Leptin, the ob-gene product released from white adipocytes, is suspected to reduce food intake mainly by acting on neurons in the arcuate nucleus of the hypothalamus. Application of orexin A activated 85% (66 out of 78) of all neurons of the rat arcuate nucleus investigated electrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 32 publications
3
24
2
Order By: Relevance
“…The putative participation of the STAT3 molecule and its mode of action in such nongenomic, fast neuronal leptin effects remains to be elucidated; however, the intense nerve fiber and axonal STAT3 labeling occurring after leptin application favors the hypothesis of an involvement of axodendritic neuronal processes in fast responses to leptin. In line with electrophysiological data, less Fos-stained than STAT3-labeled cell nuclei may indicate that leptin predominantly induces neuronal inhibition rather than activation in those structures (Spanswick et al, 1997;Rauch et al, 2000). It should be mentioned, however, that these results could also be a reflection of the 60 min time point used in the present study, it being a compromise between the peak of leptin-induced nuclear STAT3 (15-30 min) and nuclear Fos expression (90 min).…”
Section: Stat3 Immunohistochemistry: a Novel Tool To Map Neurons Respcontrasting
confidence: 42%
See 1 more Smart Citation
“…The putative participation of the STAT3 molecule and its mode of action in such nongenomic, fast neuronal leptin effects remains to be elucidated; however, the intense nerve fiber and axonal STAT3 labeling occurring after leptin application favors the hypothesis of an involvement of axodendritic neuronal processes in fast responses to leptin. In line with electrophysiological data, less Fos-stained than STAT3-labeled cell nuclei may indicate that leptin predominantly induces neuronal inhibition rather than activation in those structures (Spanswick et al, 1997;Rauch et al, 2000). It should be mentioned, however, that these results could also be a reflection of the 60 min time point used in the present study, it being a compromise between the peak of leptin-induced nuclear STAT3 (15-30 min) and nuclear Fos expression (90 min).…”
Section: Stat3 Immunohistochemistry: a Novel Tool To Map Neurons Respcontrasting
confidence: 42%
“…Although in many cases a leptin-induced direct inhibition of neuronal activity in the ARC occurred, some direct activation of neuronal activity also existed (Rauch et al, 2000). In any case, the neuronal discharge rate was rapidly changed in these experiments and therefore, at least initially, these changes occurred independently from genomic effects, e.g., the leptininduced Fos expression or gene regulation via binding of phosphorylated STAT3 dimers to distinct promoter regions.…”
Section: Stat3 Immunohistochemistry: a Novel Tool To Map Neurons Respmentioning
confidence: 83%
“…In this study the orexin-A-induced increase in the L-type Ca 2ϩ current is a modest modification rather than a marked enlargement, which makes it difficult to obtain a doseresponse curve. The release and regulatory effect of orexin-A in vivo may reflect the actions of a number of other factors from the hypothalamus, such as leptin or neuropeptide Y. GH release may be significantly influenced by hypothalamic peptides and their complex interaction (57)(58)(59). Furthermore, the distribution of orexin-1 receptor among pituitary cells is, in fact, largely unknown, and the difference between species cannot be ruled out either.…”
Section: Discussionmentioning
confidence: 92%
“…Several in vivo and in vitro studies have shown that orexins have an excitatory effect on various brain regions involved in autonomic regulation, such as the lateral and medial hypothalamus [21], the arcuate nucleus [22], and tuberomammillary nucleus [23] in the hypothalamus, the nucleus accumbens [24], and the locus coeruleus [25]. The present study demonstrates that the hypothalamic peptides orexin A and orexin B also excited the IN neurons in the cerebellum, an important subcortical motor structure primarily coordinating execution of ongoing movements.…”
Section: Discussionmentioning
confidence: 99%